Synthesis and application of iron sulfide−based materials to activate persulfates for wastewater remediation: a review - Sun, Yuqing; Liu, Jiapeng; Fan, Xiaobin; Li, Yang; Peng, Wenchao (Frontiers in Environmental Science, 2023)
Rapid industrial development has led to excessive levels of various contaminants in natural water, which poses a challenge to the innovation of environmental remediation technology. In recent years, iron sulfide and its modified materials have attracted extensive attention in environmental remediation due to their high activity in advanced oxidation processes (AOPs) and widespread existence in anoxic environment. This paper reviewed the latest advances of the synthesis methods for iron sulfide and modified FeS. In addition, the application of persulfate activation by iron sulfide materials (FeS, FeSx, S−ZVI, FeS@BC and MFexSy) for contaminants remediation is also reviewed, and the enhancement of this system by photo irradiation, ultrasound, and microwave have also been concluded. Additionally, the interaction mechanism of iron sulfide and persulfate with contaminants was reviewed. Based on the above contents, we concluded that the long−term stability of iron sulfide, the toxicity to organisms of iron sulfide materials in the treated water, and the combination of FeS/PS with other assisted technologies should be focused in future.